2016
DOI: 10.1016/j.bbagrm.2016.07.013
|View full text |Cite
|
Sign up to set email alerts
|

The miRNA biogenesis factors, p72/DDX17 and KHSRP regulate the protein level of Ago2 in human cells

Abstract: Abstract:MicroRNAs ( Here we show that the two RNA-binding proteins, p72 and KHSRP, both with known roles in promoting miRNA biogenesis, regulate the protein level of human Ago2 in transformed human cells. We determined that p72 and KHSRP influence Ago2 stability by regulating miRNA levels in the cell and that loss of p72/KHSRP results in a decrease of unloaded Ago2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In the past few decades, miRNAs have become essential post-transcriptional regulators of gene expression ( 13 , 14 ). Studies have shown that the abnormal expression of miRNA may be related to the inflammatory response in patients with neonatal sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…In the past few decades, miRNAs have become essential post-transcriptional regulators of gene expression ( 13 , 14 ). Studies have shown that the abnormal expression of miRNA may be related to the inflammatory response in patients with neonatal sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…In the past few decades, miRNA has become an essential post-transcriptional regulator in the regulation of gene expression [14][15][16].Studies have shown that the abnormal expression of miRNA may be related to the in ammatory response in patients with sepsis.For example, miR-26a is down-regulated in blood monocytes and serum in neonatal sepsis [17].As a speci c biomarker, miR-1290 provides a basis for pediatricians to diagnose NEC cases and neonatal sepsis [18]. SNHG16 is able to reverse the effect of miR-15a/16 on the LPS-induced in ammation pathway [19].But there is still a lack of an ideal biomarker for neonatal sepsis early diagnosis.Therefore, exploring new functional miRNAs is of great value for the treatment of neonatal sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, more than 1,500 RBP genes have been founded through genome-wide screening in human genome [10]. RBPs could regulate gene transcription, but mainly act on RNA processing, such as mRNA splicing, localization, polyadenylation, translocation, stability, translation [11,12], which is more rapid than transcription factors mediated regulation [13,14]. Due to the critical roles of post-transcriptional regulation in the development of biology, it is thus reasonable that functional disruption of RBPs are involved into the progression of multiple human diseases, such as U1-70K in Alzheimer's disease [15], muscleblind in neurodegeneration [16,17], FMRP in Fragile X syndrome [18] , quaking (QKI), human antigen R (HuR), and serine/arginine-rich splicing factor 1 (SRSF1) in cardiovascular disease [19].…”
Section: Introductionmentioning
confidence: 99%